Red mite (Panonychus citri) attack amplifies citrus rootstock-driven responses in physiological and biochemical traits, VOC emission, and expression of defence-related genes in mandarin scions - Rioja, Tommy; Ruiz, Karina B.; Ceballos, Ricardo (Frontiers in Plant Science, 2025)
Citriculture faces significant constraints in expanding into new environments and agroecological zones. Grafting onto tolerant rootstocks has helped overcome some of these limitations, enabling cultivation under diverse conditions. Nevertheless, citrus production remains vulnerable to multiple abiotic and biotic stressors, among which red mite (Panonychus citri) herbivory can markedly reduce yield and fruit quality. While rootstocks are known to influence scion physiology and defence capacity, their specific role in modulating responses to pest attack is still poorly understood. To address this, we evaluated 18-month-old ‘W. Murcott’ mandarin grafted onto four citrus rootstocks (‘Macrophylla’, ‘C35’, ‘Citrumelo’, ‘Carrizo citrange’) under semi-field conditions, infested or not with P. citri. After seven days of infestation (100–160 eggs/leaf), we quantified stress markers (malondialdehyde, proline, salicylic acid), physiological parameters, primary and secondary metabolites, volatile organic compounds (VOCs), and defence-related gene expression. Rootstocks significantly modulated constitutive and inducible responses. ‘Citrumelo’ and ‘Carrizo’ showed the lowest MDA accumulation and strongest induction of SA, PR5, and GLR transcripts, coupled with increased emission of herbivory-induced plant volatiles (HIPVs, e.g., β-pinene, methyl salicylate, β-ocimene). ‘Macrophylla’ exhibited limited changes, whereas ‘C35’ displayed high MDA content and PITY1 induction, suggesting greater oxidative stress. Photosynthetic pigments declined across all combinations after infestation, while soluble sugars and flavonoids decreased in susceptible rootstocks. VOC profiles shifted both qualitatively and quantitatively in a rootstock-dependent manner. These results show that P. citri herbivory can amplify rootstock-driven differences in physiological, biochemical, and molecular traits, providing a basis for further studies on the role of rootstock–scion interactions in citrus resistance to mite attack.